Koordinasi Lintas Sektor dalam Pengelolaan Daerah Aliran Sungai (DAS) Tallo di Makassar - Mursalin Mursalin; Nurasia Natsir (Student Scientific Creativity Journal, 2024)
The management of the Tallo Watershed (DAS Tallo) in Makassar City requires effective cross-sectoral coordination, given the complexity of the problems faced, such as water pollution, sedimentation, and flooding. This study aims to analyze cross-sectoral coordination in the management of the Tallo Watershed in Makassar City. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and document studies. The results show that cross-sectoral coordination in the management of the Tallo Watershed has not been optimal. There are several obstacles, such as a lack of commitment and synchronization of programs between relevant agencies, limited resources, and minimal community participation. In addition, no coordination forum functions effectively to integrate the various interests and programs of various sectors. To improve cross-sectoral coordination in the management of the Tallo Watershed, efforts are needed, including (1) strengthening the commitment and synchronization of programs between relevant agencies; (2) increasing human resource capacity and budget; (3) establishing a Tallo Watershed management coordination forum involving all stakeholders; and (4) increasing community participation in the management of the Tallo Watershed.